Impact of water availability on root growth of sugar beet varieties. (27th October 2020) - Fitters, Tamara F. J.; Mooney, Sacha J.; Sparkes, Debbie L.
Abstract: On average, sugar beet yield in the UK is reduced by 10% due to water limitation. The root system of a plant is responsible for water uptake and hence an extensive root system is crucial to mitigate drought stress. There might be varietal differences when it comes to plant root system architecture but so far none have been reported in sugar beet. This study shows the results of 2 years of field experiments, examining the rooting patterns and overall plant growth of sugar beet under both rainfed and irrigated conditions. In the first year, three varieties were assessed, and in the second year, five varieties. No significant yield differences were found between the rainfed and irrigated treatments, which is likely due to the applied drought stress only being mild in both years. There were, however, significant varietal differences in plant growth and rooting patterns in rainfed plants which were most distinct when plants were subjected to mild drought stress. Varietal differences observed might indicate the possibility of breeding for certain root traits to mitigate drought stress in sugar beet in the future.